Walking Activity during Daily Living in Children with Myelomeningocele - Yasmeh, Pauline (Disabil Rehabil, 2016)
PURPOSE: To quantify the walking activity of children with myelomeningocele during daily living. METHOD: Walking activity was measured using a StepWatch activity monitor over one week in 47 children with myelomeningocele (27 males; 9y 11mo SD 2y 7mo; 18 sacral, 9 low lumbar, 20 mid-high lumbar) and 7 children with typical development (5 males; 11y 1mo SD 1y 11mo) in a prospective, cross-sectional study. Average total steps per day, number of steps and minutes spent at low, medium and high intensity stepping were evaluated. Groups were compared using t-tests and chi-squared tests with Bonferroni post-hoc adjustment. RESULTS: Children with sacral and low lumbar myelomeningocele exhibited no significant differences in demographic characteristics or walking performance compared to typically developing children. Children with mid-high lumbar myelomeningocele exhibited higher BMI percentile than the control group (p=0.04) and took fewer total steps per day than all other groups (p≤0.04). Children with mid-high lumbar myelomeningocele also spent significantly less time taking steps at all intensity levels, particularly medium-intensity, than the sacral and low lumbar groups (p≤0.04). CONCLUSIONS: Children with sacral and low lumbar myelomeningocele had walking performance similar to typically developing children despite a common need for braces and assistive devices. Children with mid-high lumbar myelomeningocele were less active, which may lead to heightened risk for secondary health conditions in addition to those associated with myelomeningocele.